Establishing Usufruct Rights under Statutory Basis in Vietnamese Law - Hung, Le Minh (Journal of Ecohumanism, 2024)
The usufruct rights is a legal right that was imposed on the property of another person, and can only arise based on legal events prescribed by law, called the basis for establishing usufruct rights. The basis for establishing usufruct rights according to the laws of different countries is not entirely the same. In Vietnam, usufruct rights are established based on three legal bases: the basis prescribed by law, the basis of the agreement of the parties, or the basis of a will. This article studies the basis for establishing the right of usufruct according to the statutory basis, in current Vietnamese law (specifically the 2015 Civil Code). By using the methods of written law analysis, historical method, comparative legal method, and survey of the practical application of Vietnamese law, the article provides the content of positive law in Vietnam on the basis for establishing usufruct rights according to the law, aiming to introduce readers to the current legal status, point out the advantages and disadvantages of these regulations, select practical experiences of foreign law, and contribute to building solutions to improve the regulations on the basis for establishing usufruct rights according to the law in Vietnam today.